Programa de educación sexual para promover una sexualidad responsable en los adolescentes del octavo año paralelo a, de la escuela de educación básica Miguel Riofrio Nº2, 2013 – 2014. - Iñiguez Mendieta, Viviana Paola (2016)
The school as a formal educational agent, has not only the duty if not ethical and legal obligation to provide students with the necessary training to be able to live their sexuality in a healthy and satisfactory manner; for this reason qualification for this work he was raised as a general objective Implement a program of sex education to promote responsible sexual behavior in adolescents parallel eighth year A, School of Basic Education Miguel Rriofrío No. 2, 2013-2014 It was a descriptive cross-sectional study design and experimental Causi; the methods used were scientific, deductive, inductive, historical; descriptive, logical, comprehensive, statistical, diagnostic and modeling, the questionnaire C.A.S Rodriguez & Farre was used. The results in terms of knowledge, 55.56% evidence erroneous knowledge about sexual education and 77.7% manifest inappropriate attitudes (pretest) after intervention 83.3% significantly improves their knowledge and attitudes in a 16.67% (posttest). The sex education program reached values r (x, y) = 0.90 in knowledge and attitudes r (x, y) = 0.49 with high and moderate positive correlation respectively. It was concluded that there were not adequate for the lack of knowledge attitudes, but managed to modify them through the sex education program. .